Google Books Corpus and designing English for specific purposes materials - Munassir Alhamami (Journal on English as a Foreign Language, 2022)
Designing language-learning materials that target the needs of specific groups of students can be a challenge because students' needs vary. There is a research gap in identifying learning materials that meet the needs of a specific group of students. The study objective is to utilize open educational resources to design English for specific purposes (ESP) materials. The study implements a corpus linguistics method by using the Google Books Corpus (GBC) to develop language-learning materials for engineering students. The application analyzed the corpora by frequency that was the default analysis procedure in GBC. The findings show the procedures to create English grammar materials for engineering students and engineers who need to improve their knowledge about the commonly used grammar structures in engineering texts. The results of analyzing GBC present five chapters: nouns, verbs, adjectives, adverbs, and prepositions that are commonly used in engineering texts using authentic examples. The findings demonstrate the importance of corpus technologies such as GBC in language learning classrooms. The implication is that language educators should utilize open educational resources such as GBC to provide students with learning materials that have authentic examples, commonly used words, and widely used grammar structures in the students' academic majors.